PAESAGGIO LINGUISTICO, VARIAZIONE E TRASFORMAZIONI SOCIALI: Contributi di Marcella Uberti-Bona, Martina Bellinzona, Roberta Garruccio, Cristina Dozio, Marco Golfetto, Federico Pozzoli, Giuseppe Sergio, Lorenzo Cambi, Simone Ferrari, Carla Bagna (Italiano LinguaDue, 2024)
Monografia